Effect of Curing Time on Polymerization Rate of Bulk-Fill Composite Resins - Jaberi Ansari, Zahra; Ghasemi, Amir; Vatandoust, Mohammad Taghi; Kalantar Motamedi, Mojdeh (Journal of Dental School, 2019)
Objectives: The aim of this study was to compare polymerization depth of two bulk-fill and one conventional composite cured for different times. Methods: This in vitro experimental study was conducted on 54 composite samples (2×4×10mm) fabricated of Tetric N-Ceram bulk-fill, x-tra fil bulk-fill, and Grandio conventional composite cured for 20, 30, and 40 seconds. The microhardness of samples was measured at 0.1, 2, 2.5, 3, 3.5, 4, and 4.5mm depths using a Vickers hardness tester. The results were analyzed using ANOVA, t-test, and Tukey’s test. Results: The x-tra fil, Tetric N-Ceram and Grandio had maximum microhardness at 0.1mm depth after curing for 40 seconds. The microhardness decreased as the depth of composite increased. Microhardness of x-tra fil was higher than that of Tetric N Ceram. By increasing the curing time, the microhardness value of x-tra fil significantly increased up to 2mm depth. In Tetric N-Ceram, by increasing the curing time from 20 to 30 seconds microhardness increased significantly (P<0.05) by up to 3.5mm depth. By increase from 20 to 30 seconds, no significant change occurred in microhardness of Grandio samples at 0.1 and 2mm depths, but further increase from 30 to 40 seconds significantly increased the microhardness at all depths (P<0.05). Conclusion: The maximum microhardness was obtained for x-tra fil at 0.1mm depth following 40 seconds of curing. Microhardness in deep areas (>2mm depth) depends on the type of composite, curing time and depth. Overall, 20 seconds of curing for x-tra fil and 30 seconds for Tetric N-Ceram seem appropriate.